Miracles and extraordinary experience in northern Kenya - Straight, Bilinda, 1964- (Contemporary ethnography., 2007)
The miraculous blends with the mundane in this book as the Samburu continue their day-to-day twenty-first-century existence. Straight describes miracles inside the cultural logic that makes them possible, questioning how anthropology can best engage with the improbable.